Understanding Tax Policy Research in Indonesia: A Bibliometric Perspective - Perdana, Gusti Naufal Rizky; Haliza, Elza Fatika Nur (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study aims to conduct a bibliometric analysis of tax policy in Indonesia, focusing on identifying research trends, dominant issues, and emerging research themes in this field. Data obtained from the Scopus database using the keywords